The Philippine Tariff Structure: An Analysis of Changes, Effects and Impacts - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1999)
Recently, one of the most highly controversial reforms implemented in the Philippines is the trade reform program. It includes tarrification of quantitative restrictions, the simplification of tariff rates structure and the reduction in the tariff protection. This paper discusses the effects of the program on the tariff structure and its impact on resource allocation, on income distribution and on household in terms of food availability. Analysis is based on survey of literature and on a set of model simulations using economy-wide model of the Philippines.
Keywords: 330; tariff; trade sector; tariff structure; economy-wide model